Guidelines for perioperative care in cataract surgery in Poland - Jacek P. Szaflik; Alina Bakunowicz-Łazarczyk; Dariusz Dobrowolski; Iwona Grabska-Liberek; Bartłomiej Kałużny; Jakub Kałużny; Wojciech Lubiński; Jerzy Mackiewicz; Katarzyna Michalska-Małecka; Marta Misiuk-Hojło; Ewa Mrukwa-Kominek; Agnieszka Nowak; et al. (Klinika Oczna)
The approach to cataract surgery procedures in Poland has changed significantly over the past few years. The authors outline the current principles of perioperative care in cataract surgery